2016
DOI: 10.1038/nature17671
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies 74 loci associated with educational attainment

Abstract: SummaryEducational attainment (EA) is strongly influenced by social and other environmental factors, but genetic factors are also estimated to account for at least 20% of the variation across individuals1. We report the results of a genome-wide association study (GWAS) for EA that extends our earlier discovery sample1,2 of 101,069 individuals to 293,723 individuals, and a replication in an independent sample of 111,349 individuals from the UK Biobank. We now identify 74 genome-wide significant loci associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,487
6
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,265 publications
(1,574 citation statements)
references
References 16 publications
63
1,487
6
8
Order By: Relevance
“…The HRS is well-equipped for this purpose. It is used as a validation sample in several recent GWAS 33,43 and it would be possible to test the robustness of replication results to mortality selection. The empirical evidence presented with respect to height and BMI suggest that such resulting biases may be small, but mortality bias may be more pernicious in other contexts, especially in studies of traits with clear mortality associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRS is well-equipped for this purpose. It is used as a validation sample in several recent GWAS 33,43 and it would be possible to test the robustness of replication results to mortality selection. The empirical evidence presented with respect to height and BMI suggest that such resulting biases may be small, but mortality bias may be more pernicious in other contexts, especially in studies of traits with clear mortality associations.…”
Section: Discussionmentioning
confidence: 99%
“…Polygenic scores were computed from the genome-wide SNP database using published results [30][31][32][33] from the original genome-wide association studies (GWAS) using the most recent PGS techniques. 34 (Because the GWAS of educational attainment included HRS, we obtained a revised set of results based on meta-analysis excluding HRS.)…”
Section: Polygenic Scoresmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have shown many genomic associations with a wide array of complex phenotypes and have allowed detection of signals of genetic adaptation (54). However, GWA studies of behavioral phenotypes such as IQ, educational attainment, and life history should be interpreted with care (55)(56)(57)(58). As the authors of one such study state: "Studies of genetic analyses of behavioural phenotypes have been prone to misinterpretation, such as characterizing identified associated variants as 'genes for education.'…”
Section: Human Genesmentioning
confidence: 99%
“…Additional analyses were also performed on the two smaller POLY COG (11 and 9 SNPs) using two unconditional tests (considered more powerful alternatives); specifically, Barnard's (1945Barnard's ( , 1947) and Boschloo's (1970) Exact tests, utilizing the R package Exact (Calhoun, 2016). In constructing POLY COG for conventional GWAS-type analyses, it is common practice to weight each SNP by its associated GWAS regression β value, as these polygenic scores are typically the sum of very large numbers of SNPs with highly heterogeneous effect sizes as predictors of the phenotype of interest (e.g., Okbay et al, 2016). These regression weights were not found to significantly correlate with the frequency differences between modern and ancient populations for the largest of our POLY COG , however (130 SNP; r = -0.128, p = .07), likely because selecting only the SNPs with the highest p values introduced range restriction among the regression weights.…”
Section: Resultsmentioning
confidence: 99%
“…High-resolution genome-wide association studies (GWAS) have identified a number of single nucleotide polymorphisms (SNPs) primarily associated with the development of the central nervous system that predict variance in both GCA and educational attainment-with which GCA shares approximately 60% of its linkagepruned genetic variance (Davies et al, 2016;Domingue et al, 2015;Okbay et al, 2016;Rietveld et al, 2013Rietveld et al, , 2014Selzam et al, 2017). These SNPs can be concatenated into cognitive polygenic scores (henceforth POLY COG ).…”
mentioning
confidence: 99%